Mechanical Behavior of Concrete Pavement considering Void beneath Slabs and Joints LTE - Bangyi Liu; Yang Zhou; Linhao Gu; Dalin Wang; Xiaoming Huang (Advances in Civil Engineering)
Dowel bars are arranged between two slabs of jointed plain concrete pavements to transfer load between them. The looseness of these dowel bars leads to the decrease of the load transfer efficiency (LTE). Meanwhile, repeated vehicle load can result in void near the joints. In this paper, the behaviors of concrete pavement under the effect of void size and joint stiffness were studied by using ABAQUS software. The FEA model was calibrated for different element parameters based on mesh convergence analysis and validated by comparison with previous studies. The voids beneath slabs were considered in this study, including the loaded slab and unloaded slab. The different effects of base course modulus on the stress of loaded slab are also analysed. It is concluded that the results show that the void size and joint stiffness affect the stress of the loaded plate. Smaller void size and larger joint stiffness will lead to the maximum stress located at the bottom of the loaded slab, and the void size has little effect on the stress of the loaded slab. Otherwise, the larger void size will cause larger stress. The effect of base modulus on stress is similar.